The stability of the hip after the use of a proximal femoral endoprosthesis for oncological indications: analysis of variables relating to the patient and the surgical technique. (April 2017) - Henderson, E. R.; Keeney, B. J.; Pala, E.; Funovics, P. T.; Eward, W. C.; Groundland, J. S.; Ehrlichman, L. K.; Puchner, S. S. E.; Brigman, B. E.; Ready, J. E.; Temple, H. T.; Ruggieri, P.; et al.
Abstract : Aims: Instability of the hip is the most common mode of failure after reconstruction with a proximal femoral arthroplasty (PFA) using an endoprosthesis after excision of a tumour. Small studies report improved stability with capsular repair of the hip and other techniques, but these have not been investigated in a large series of patients. The aim of this study was to evaluate variables associated with the patient and the operation that affect post-operative stability. We hypothesised an association between capsular repair and stability. Patients and Methods: In a retrospective cohort study, we identified 527 adult patients who were treated with a PFA for tumours. Our data included demographics, the pathological diagnosis, the amount of resection of the abductor muscles, the techniques of reconstruction and the characteristics of the implant. We used regression analysis to compare patients with and without post-operative instability. Results: A total of 20 patients out of 527 (4%) had instability which presented at a mean of 35 days (3 to 131) post-operatively. Capsular repair was not associated with a reduced rate of instability. Bivariate analysis showed that a posterolateral surgical approach (odds ratio (OR) 0.11, 95% confidence interval (CI) 0.02 to 0.86) and the type of implant (p = 0.046) had a significant association with reduced instability; age > 60 years predicted instability (OR 3.17, 95% CI 1.00 to 9.98). Multivariate analysis showed age > 60 years (OR 5.09, 95% CI 1.23 to 21.07), female gender (OR 1.73, 95% CI 1.04 to 2.89), a malignant primary bone tumour (OR 2.04, 95% CI 1.06 to 3.95), and benign condition (OR 5.56, 95% CI 1.35 to 22.90), but not metastatic disease or soft-tissue tumours, predicted instability, while a posterolateral approach (OR 0.09, 95% CI 0.01 to 0.53) was protective against instability. No instability occurred when a synthetic graft was used in 70 patients. Conclusion: Stability of the hip after PFA is influenced by variables associated with the patient, the pathology, the surgical technique and the implant. We did not find an association between capsular repair and improved stability. Extension of the tumour often dictates surgical technique; however, our results indicate that PFA using a posterolateral approach with a hemiarthroplasty and synthetic augment for soft-tissue repair confers the lowest risk of instability. Patients who are elderly, female, or with a primary benign or malignant bone tumour should be counselled about an increased risk of instability. Cite this article: Bone Joint J 2017;99-B:531–7.